ADENOMA PLEOMÓRFICO EM LÁBIO SUPERIOR: RELATO DE CASO DE APRESENTAÇÃO CLÍNICA ATÍPICA - Silva, Andryel Pinheiro Massena da (2023)
Introduction: pleomorphic adenoma (PA) is a benign neoplasm that affects the salivary glands and presents remarkable histopathological variety. Objective: to report the case of a PA with atypical clinical presentation in the upper lip. Case report: an 88-year-old woman sought dental care complaining of an asymptomatic swelling in her upper lip, which had been evolving for 2 years. The physical examination showed a swelling of ill-defined limits, sessile, with normochromic and reddish areas, telangiectasias, an ulcerated surface, in the upper labial mucosa and the vestibule on the left side, in addition to notable facial asymmetry. With diagnostic hypothesis of salivary gland malignancy, an incisional biopsy was performed. Microscopically, a glandular neoplasm composed of ductal epithelial cells and myoepithelial cells with multiple ductal formations was observed, present in a loose and cartilaginous stroma. Computed tomography showed a large and extensive lesion with a density compatible with soft tissues, without foci of calcification or involvement of bone structures. Based on clinical, imaging and histopathological criteria, the final diagnosis was PA. The patient underwent total excision of the lesion in a hospital setting. The 6-month postoperative evaluation showed no recurrence of the lesion and significant improvement in facial appearance.  Conclusion: PA should be considered as a diagnostic hypothesis for slowly growing swellings in the upper lip, even if they present ulcerated and telangiectatic areas.